Spatial analysis of pentavalent immunobiological vaccine coverage in children under one year of age - Juliane Maria Guedes de Carvalho; Beatriz Jorge Oliveira Gomes; Gláucia Maria Canato Garcia; Lucas Vinícius de Lima; Edileuza de Fátima Rosina Nardi; Mayckel da Silva Barreto; Sonia Silva Marcon (Rev Rene)
Objective: to analyze the spatial distribution of pentavalent immunobiological vaccine coverage in children under one year of age. Methods: this is an ecological time series study which used data from the National Immunization Program Information System on the pentavalent vaccine coverage rate in a southern Brazilian state, between 2013 and 2022. Vaccination coverage was expressed in percentages, by year, health region and immunobiological type. In addition, distribution and spatial autocorrelation analyses of municipal rates were used. Results: the average pentavalent vaccination coverage in the state was 90.94%, with the highest rate in 2013 (101.94%) and the lowest in 2019 (79.03%). The Western macroregion had the highest average coverage, while the Northern macroregion had the lowest. Low coverage clusters were evident in the Eastern region. Conclusion: vaccination coverage in Paraná has been decreasing over the years, possibly due to the rise of anti-vaccine movements and the impact of the pandemic in the last three years. Contributions to practice: the results highlight the need for awareness campaigns and targeted actions for regions with low vaccination coverage. Health professionals, especially nurses, can use these data for interventions which promote greater vaccination adherence.